2010
DOI: 10.4038/cmj.v55i1.1701
|View full text |Cite
|
Sign up to set email alerts
|

Association between HER-2/neu over-expression and clinico-pathologic parameters of breast cancer in northern Malaysia

Abstract: Background Breast cancer is the commonest cancer affecting women world wide. Breast cancer is a leading cause of cancer related mortality in Asian countries. Management of breast cancer depends on several tumour-related and patient related factors. HER-2/neu over-expression has been associated with a poor prognosis in breast cancer. We assessed HER-2/neu over expression pattern in unselected breast cancer cases in terms of clinico-pathologic parameters to identify any associations between them. Methods Two hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This finding was further supported by a group from Indore city Central India which showed 40.2% positivity and Varanasi city from Northern India exhibited 46.3% positivity (Kumar et al, 2007;Munjal et al, 2009). Reports from Asian , 2006;Naeem et al, 2008;Kamil et al, 2010). Studies from USA have reported that 17-27% of the BC patients are positive for HER-2/neu expression (Taucher et al, 2003;Huang et al, 2005;Lal et al, 2005), while 15-20% of BC cases were reported to be HER-2/neu positive in UK (Lovekin et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was further supported by a group from Indore city Central India which showed 40.2% positivity and Varanasi city from Northern India exhibited 46.3% positivity (Kumar et al, 2007;Munjal et al, 2009). Reports from Asian , 2006;Naeem et al, 2008;Kamil et al, 2010). Studies from USA have reported that 17-27% of the BC patients are positive for HER-2/neu expression (Taucher et al, 2003;Huang et al, 2005;Lal et al, 2005), while 15-20% of BC cases were reported to be HER-2/neu positive in UK (Lovekin et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent study, overexpression of HER2 protein in two hundred patients in northern Malaysia was not significantly associated with age but that a high percentage (i.e.75%) of overexpression was noted in the age group 81-85 years [164]. Higher rates of HER2 overexpression in postmenopausal women were also seen in breast cancer patients in the south of Switzerland [170].…”
Section: Her2 Statusmentioning
confidence: 93%
“…Another cohort study with 1,359 cases reported that 35.1% of breast cancers in Vietnamese patients had HER2 protein overexpression which is considerably higher compared to results from Western countries [149] [164]. A protein overexpression of HER2 was detected in 32% and gene amplification in 37.5% of cases reported in breast cancers from Thailand [41,165].…”
Section: Her2 Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive ER and PR status was determined when immunostaining was positive in ≥ 1% of the cells [ 42 ]. HER2−positive cancers were defined by either strong membrane staining (3+) observed by IHC or amplification of HER2 confirmed by fluorescence in situ hybridization when immunohistochemistry detected moderate (2+) membrane staining [ 43 ].…”
Section: Methodsmentioning
confidence: 99%